A Combined Notion of Traffic, Bandwidth and Congestion Adaptive Rate Adjustment Algorithm for WSNs - V. Priya, Dr. S. Mohanapriya (International Journal of Advanced Science and Technology, 2020)
In Real-Time (RT) applications, Wireless Sensor Networks (WSNs) encompass different kinds of data. Because of the bandwidth constraints, such kinds of data should be controlled with different priorities to prevent the congestion in a network. Many algorithms have been developed on the basis of traffic class priority to prevent the congestion by computing the rate variation at any node. In contrast, WSN frequently wants to handle the combination of RT and Non RT (NRT) data. For this purpose, Weighted Priority Difference of Differential Rate Control (WPDDRC) algorithm was developed for handling the mixture of RT and NRT data via combining WP of the traffic class and the DDR of a certain node. Nonetheless, it requires to enhance the adjustment of transmission rate adaptively by means of the combined notion of the traffic class priority and the fair distribution of bandwidth including the Active Queue Management (AQM) for avoiding the congestion. Therefore, this article proposes a Combined Traffic, Bandwidth and Congestion Adaptive Rate Control (CTBCARC) algorithm. In this algorithm, the notion of DDRs of a particular node is considered including the traffic class priority, fair distribution of bandwidth and AQM. The weighted fair queue scheduler and the mean input bandwidth of different traffic class priorities are applied for minimizing the congestion by fairly distributing the bandwidth. Besides, every node allocates the bandwidth requests and grants in a round-robin fashion. Moreover, each active queue is decided a weight value for controlling the traffic load and preventing the congestion in WSNs. Finally, the simulation outcomes demonstrate that the effectiveness of CTBCARC algorithm than the WPDDRC and DDRC algorithms. Keywords: Wireless sensor networks, Congestion avoidance, Rate control, Traffic class priority, WPDDRC, Fair bandwidth allocation, AQM